2021
DOI: 10.1155/2021/6641919
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effects of Water Extracts of Compound Turmeric Recipe on Acute Alcoholism: An Experimental Research Using a Mouse Model

Abstract: Acute alcoholism (AAI) is a common emergency. Currently, there is a lack of preventive and therapeutic drugs with superior safety and efficacy. Curcuma longa, Panax ginseng, Pueraria lobata, Pueraria flower, and Hovenia dulcis Thunb., which are the components of compound turmeric recipe (CTR), are, respectively, used in China as adjuvant therapeutic agents for AAI and alcoholic liver injury, respectively. The purpose of this research was to investigate the effect of traditional compound turmeric recipe in anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…These observations indicate that supplementation of turmeric extract enhances alcohol clearance, reducing hangover symptoms. Additionally, curcumin, a major component in turmeric extract, could help to relieve hangover symptoms ( Liang et al., 2021 ). In humans, turmeric extract and curcumin showed lower blood acetaldehyde levels and reduced discomfort, indicating the inhibitory effects on alcohol intoxication ( Liang et al., 2021 ; Sasaki et al., 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations indicate that supplementation of turmeric extract enhances alcohol clearance, reducing hangover symptoms. Additionally, curcumin, a major component in turmeric extract, could help to relieve hangover symptoms ( Liang et al., 2021 ). In humans, turmeric extract and curcumin showed lower blood acetaldehyde levels and reduced discomfort, indicating the inhibitory effects on alcohol intoxication ( Liang et al., 2021 ; Sasaki et al., 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, curcumin, a major component in turmeric extract, could help to relieve hangover symptoms ( Liang et al., 2021 ). In humans, turmeric extract and curcumin showed lower blood acetaldehyde levels and reduced discomfort, indicating the inhibitory effects on alcohol intoxication ( Liang et al., 2021 ; Sasaki et al., 2011 ). The hangover symptoms, including physical and mental symptoms, typically occur in individuals when alcohol consumption exceeds 1.0 g ethanol/kg ( Piasecki et al., 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Before the experiment began, all rats fasted for 18 h and drank freely. The model and treatment groups were given 14 ml kg −1 ( Liang et al, 2021 ) 56°liquor by gavage, while the control and puerarin groups were given an equal volume of distilled water. After 30 min, the treatment and puerarin groups were given 200 mg kg −1 ( Keskin Alkaç et al, 2022 ) puerarin by gavage, and the same amount of distilled water was given to both the control and model groups.…”
Section: Methodsmentioning
confidence: 99%
“…Alcoholism has become a severe public health problem in recent years, with epidemiology indicating that approximately 2.5 million people die yearly from excessive drinking ( Liang et al, 2021 ). Acute alcoholism is a condition in which a single large dose of alcohol causes the blood ethanol content to become too high, resulting in multiple organ dysfunctions and metabolic disorders ( Vonghia et al, 2008 ; Yu and Ji, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the use of compound turmeric recipe increased the activities of alcohol dehydrogenase, aldehyde dehydrogenase, cytochrome P450, and SOD while decreasing the contents of TNF‐α, IL‐8, and MDA in the liver. The activities of ALT, AST, and ALP in serum were also lowered (Liang et al, 2021). Concurrent administration of ethanol and fermented C. longa (contains greater amounts of tetrahydrocurcumin and caffeic acid than C. longa ) resulted in increased levels of carnitine palmitoyltransferase 1 (CPT‐1), peroxisome proliferator‐activated receptor‐alpha (PPAR‐α), and AMP‐activated protein kinase.…”
Section: Effect Of Turmeric and Curcumin On Ethanol Toxicitymentioning
confidence: 99%